Standing on the shoulders of science - Joshua L. Krieger; Monika Schnitzer; Martin Watzinger (Strategic Management Journal, 2024)
Research Summary:Today's innovations rely on scientific discoveries of the past, yet only some corporate R&D builds directly on scientific output. In this article, we analyze U.S. patents to investigate how firms generate value by building on prior art "closer" to science. We show that patent value is decreasing in distance-to-science. Overall, we find a science premium within firms ranging from 5.0 to 18.3%. If we allow for firm sorting into different modes of R&D based on their relative advantage, that is, when we do not control for firm fixed effects, we find an even larger science premium: patents building directly on scientific publications are 4.0–42.3% more valuable than patents in the same technology that are not directly based on science. Managerial Summary: Building on scientific research allows firms to capture significantly more value from their inventions. By analyzing U.S. patents and their linkages to scientific publications, our paper describes the relationship between invention "proximity" to the scientific literature and public firm valuations—as measured in abnormal stock market returns. Our findings indicate that patents building on science are 5.0–18.3% more valuable. If we account for variations in R&D strategies among firms, the premium becomes even larger, ranging from 4.0 to 42.3%. Further, the results show that the value-enhancing benefits of integrating scientific insights into R&D are greater for firms with more experience building on science. Together, the results underscore the competitive advantages of using science as a foundation for corporate innovation.
Keywords: 330; innovation; intellectual property; research and development; science; technology transfer